The rps15-rpl32 intergenic locus is a phylogeographic marker for Latin American Zea mays landrace varieties and subspecies - Luciano Univaso; Francisca Peña; Celián Román-Figueroa; Manuel Paneque (BMC Genomics)
Abstract Background Maize (Zea mays L.) has a deep cultural significance in Latin America, with traditional and native varieties cultivated for millennia. Approximately 220 maize races have been identified in the region. These races have adapted to the diverse environmental conditions, resulting in a considerable diversity of varieties. Although DNA barcoding is widely used for species identification, distinguishing between varieties within a species remains challenging in plants, owing to the conserved nature of standard barcoding loci. Intragenic marker combinations are often used to address this limitation. However, they remain insufficient for variety-level resolution. Therefore, we developed a pipeline to identify robust markers that can distinguish maize varieties based on their phylogeographic origins. Results In this study, the small single-copy (SSC) region of the chloroplast genome exhibited the highest mutation rate per nucleotide. Furthermore, the intergenic regions rps15-rpl32 and ndhD-ndhF exhibited the highest mutation rates in the SSC. Comparatively, the coding genes in this region were more conserved. The rps15-rpl32 locus demonstrated improved resolution for phylogeographic analysis when concatenated with a short genetic anchor sequence. This marker accurately identified the geographic origin of maize samples. Overall, it was the most informative marker despite its relatively low SNP and InDel frequency and moderate divergence levels. Contrastingly, the ndhF-ndhD locus exhibited higher mutation rates but failed to effectively resolve phylogenetic relationships. Conclusions Our findings demonstrate that concatenated loci can accurately identify the geographic origin of Zea mays varieties and subspecies and elucidate their relationships. Moreover, the superior performance of rps15-rpl32 in the delineation of phylogenetic relationships among regional genomes shows its potential application as a marker for distinguishing closely related varieties and subspecies. This locus can facilitate the streamlined validation of Zea mays varieties for regional authenticity.